Role and functions of the national human rights institutions in transitional countries with respect to paris principles - Baishina, L. (Право и государство, 2013)
The article observes legal status, role and functions of the National Human Rights Institutions (NHRI), in transition countries, based on the experience of CIS countries with respect to Paris Principles (1993) as set of international standards, that frame and guide the work of NHRIs. It is emphasized that there is no ideal or single accepted structure for NHRIs. At the same time the national human rights institutions have to comply with the general criteria, such as independence, human rights mandate, adequate funding, and transparent selection and appointment process.
Keywords: human rights; national institutions; Paris Principles; international human rights instruments; human rights commission; ombudsman; legal status; Research Subject Categories::LAW/JURISPRUDENCE